2010
DOI: 10.1002/jmv.21957
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of human respiratory syncytial virus subgroups A and B identified in adults with hematological malignancy attending an Irish hospital between 2004 and 2009

Abstract: Human respiratory syncytial virus (HRSV) is an important cause of respiratory infection in patients with hematological malignancy, particularly hematopoietic stem cell transplant recipients. This study investigated the genetic variability of the attachment (G) protein gene among HRSV isolates collected from adult patients with hematological malignancy. Between December 2004 and March 2009, 60 samples collected from 58 adults attending an Irish hospital were positive for HRSV by direct immunofluorescence. Nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…GA2 and GA5 co-circulated in two different seasons (1998 and 2006) after which apparently only GA2 persisted, still infecting people in the Milwaukee area in 2010. These results are consistent with other published studies for RSV A [29], [46] where they also had shown that several genotypes are present now, were present in 1996, and were even present much earlier as can be seen by the fact that published sequences from as far back as 1956 fall into these same genotypes (Figure 3). These genotypes appear to have much more distant origins and continue to co-circulate with each genotype steadily accumulating unique mutations.…”
Section: Discussionsupporting
confidence: 93%
“…GA2 and GA5 co-circulated in two different seasons (1998 and 2006) after which apparently only GA2 persisted, still infecting people in the Milwaukee area in 2010. These results are consistent with other published studies for RSV A [29], [46] where they also had shown that several genotypes are present now, were present in 1996, and were even present much earlier as can be seen by the fact that published sequences from as far back as 1956 fall into these same genotypes (Figure 3). These genotypes appear to have much more distant origins and continue to co-circulate with each genotype steadily accumulating unique mutations.…”
Section: Discussionsupporting
confidence: 93%
“…The GB13 genotype, first detected in Belgium in 2001/2002 has replaced all other genotypes and co-circulated with GB12 in the season 2002/2003 and 2006/2007. This gradual replacement of circulating genotypes by GB13 has been observed in different countries and GB13 represents 100% of the isolated HRSV-B strains after 2006 [25], [28]. Since 2006/2007, GA2 has been predominating over GA5, whereas the genotype distribution pattern of the previous seasons (1996/1997–2005/2006) demonstrated annual or biennial replacement of GA5 by GA2 or vice versa.…”
Section: Discussionmentioning
confidence: 74%
“…GA2 and GA5 are characterised by genotype specific amino acid mutations [24], [25]. All Belgian GA2 strains had the previous reported T269 and S289 amino acid substitution (Figure S1).…”
Section: Resultsmentioning
confidence: 94%
“…It has also been reported in Europe and Asia [12,29,30]. The rapid and worldwide spread of the BA genotype implies that it may have a selective advantage over other circulating strains [31]. However, there may be mutations elsewhere in the genome that confer more efficient replication when compared with other RSV-B genotypes.…”
Section: Discussionmentioning
confidence: 99%